Utilizing of Sugar Refinery Waste (Cane Molasses) for Production of Bio-Plastic Under Submerged Fermentation Process - Tripathi A.D.; Yadav A.; Jha A.; Srivastava S.K. (My University, 2025)
In the present study, depending upon the availability and cheaper cost, different carbon source were tested for the production of PHAs (Polyhydroxyalkonoates) by soil bacterium Pseudomonasaeruginosa and it was found that sugar refinery waste (cane molasses) produced the maximum PHA (biodegradable polymer) which is precursor for bio-plastic development. Urea served as potent nitrogen source over other inorganic nitrogen sources in bio-plastic synthesis. Effect of different physical parameters viz; pH, temperature and agitation speed were also studied on PHA production. Batch cultivation kinetics under optimized cultural and physical condition showed maximum cell mass and PHA concentration of 7. 32 ± 0. 2 and 5. 60 ± 0. 3 g/L, respectively after 54. 0 h of cultivation. Sugar refinery waste (Total sugar 4%) and urea (0. 8%) improved the economics of the process which exhibited a yield (Y P/X) of 0. 70 with productivity of 0. 11 g/L/h. PHA was further characterized as PHB by using Fourier Transform Infra-red Spectroscopy (FT-IR). © 2011 Springer Science+Business Media, LLC.